2010
DOI: 10.1038/nsmb.1801
|View full text |Cite
|
Sign up to set email alerts
|

Human RNA polymerase III transcriptomes and relationships to Pol II promoter chromatin and enhancer-binding factors

Abstract: RNA polymerase (Pol) III transcribes many noncoding RNAs (e.g. tRNAs) important for translational capacity and other functions. Here, we localized Pol III, alternative TFIIIB complexes (BRF1/2) and TFIIIC in HeLa cells, determining the Pol III transcriptome, defining gene classes, and revealing ‘TFIIIC-only’ sites. Pol III localization in other transformed and primary cell lines revealed novel and cell-type specific Pol III loci, and one miRNA. Surprisingly, only a fraction of the in silico-predicted Pol III l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
351
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(379 citation statements)
references
References 47 publications
23
351
5
Order By: Relevance
“…Genome-wide analysis of Pol III promoter occupancy in HeLa cells suggested promoter accessibility to be a major regulator of Pol III transcription (53). This was also observed in vitro.…”
Section: Discussionmentioning
confidence: 68%
“…Genome-wide analysis of Pol III promoter occupancy in HeLa cells suggested promoter accessibility to be a major regulator of Pol III transcription (53). This was also observed in vitro.…”
Section: Discussionmentioning
confidence: 68%
“…For each experiment at each tissue and developmental stage, we performed two biological replicates that were highly correlated Methods). This approach allowed us to quantify expression levels for protein-coding genes, as well as Pol III occupancy at every tRNA locus, which quantitatively captures the utilization of each tRNA gene (Barski et al 2010;Moqtaderi et al 2010;Oler et al 2010;Kutter et al 2011;Canella et al 2012;Carriere et al 2012;Renaud et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that active chromatin coincides with active transcription of Pol III genes (Barski et al 2010;Oler et al 2010). We therefore used previously published data (Shen et al 2012) to compare the occurrence of three histone marks associated with transcriptionally active chromatin modifications, histone H3 lysine 27 acetylation (H3K27ac), H3 lysine 4 tri-(H3K4me3) and monomethylation (H3K4me1), Pol II, and the insulator-binding protein CCCTC-binding factor (CTCF) at genomic localizations 0.1, 0.5, and 1.0 kb near differentially expressed tRNA genes (Shen et al 2012;Methods).…”
Section: Stable Isoacceptor Anticodon Abundance Through Development Imentioning
confidence: 99%
See 2 more Smart Citations